Cellular and humoral biomarkers of Bronchopulmonary Dysplasia. (February 2017) - Lal, Charitharth Vivek; Ambalavanan, Namasivayam
Abstract: The pathogenesis of Bronchopulmonary Dysplasia (BPD) is multifactorial and the clinical phenotype of BPD is extremely variable. Predicting BPD is difficult, as it is a disease with a clinical operational definition but many clinical phenotypes and endotypes. Most biomarkers studied over the years have low predictive accuracy, and none are currently used in routine clinical care or shown to be useful for predicting longer-term respiratory outcome. Targeted cellular and humoral biomarkers and novel systems biology 'omic' based approaches including genomic and microbiomic analyses are described in this review.